Policy and prophecy. The legend of the last emperor and the iconography of the ruler crowned by angels in Wallachia - Negrău Elisabeta (Zograf, 2019)
The article analyses the occurrence of the iconography of the ruler crowned by angels in Wallachia in the mid-sixteenth century, a late revival of a Byzantine iconographic model with no examples known in Wallachia prior to this date. In the nave of the infirmary chapel of Cozia Monastery (1543), voivode Radu Paisie is depicted crowned by an angel and blessed by Saint Methodius of Patara, an iconographical hapax. The key for decoding the scene is provided by the Pseudo-Methodian Apocalypse, where a coronation by angels episode is found in the legend of the Last Christian Emperor. The frescoes were made in a political climate when anti-Ottoman war plans intensified in Central Europe following the occupation of Buda.